Characteristics of HIV pre-exposure prophylaxis users at first PrEP counselling visit: the CSL-PrEP cohort - Diana Canetti; Antonella Castagna; Marco Ripa; Angelo Roberto Raccagni; Elena Bruzzesi; Silvia Nozza; Laura Galli; Francesca Alberton; Riccardo Lolatto; Daniele Ceccarelli; Martina Strano; Costanza Bertoni (BMJ Open)
Objectives Pre-exposure prophylaxis (PrEP) is effective for HIV prevention and is mostly used by men who have sex with men (MSM). The aim of this study was to describe the characteristics of a cohort of PrEP users at first PrEP counselling visits (baseline, BL).Design Cross-sectional study of a cohort of MSM receiving PrEP (Centro San Luigi, CSL-PrEP Cohort).Setting Secondary-level sexually transmitted infections (STI) centre in Milan, Italy, from May 2017 to May 2022.Participants Overall, 624 MSM PrEP users were included; most users were Caucasian (97%), attended university (64%), with a median BL age of 34.5 years.Results Overall, 45% choose the daily-based PrEP regimen, 55% the event-based one. An increasing trend in PrEP counselling visits was observed (p=0.024). The majority had between 10 and 19 partners in the 3 months before BL and 41% were chemsex users. All had a HIV Incidence Risk Index for MSM (HIRI-MSM)>10, 54% between 20 and 29. Overall, 50% had ≥1 previous STI and 22% ≥1 BL STI. BL chlamydia (10%) was often more frequent than in the past (7%). The number of sexual partners was associated with BL chlamydia (p<0.001), gonorrhoea (p=0.002) and syphilis (p=<0.001), HIRI-MSM with chlamydia (p=0.001) and gonorrhoea (p=0.008), chemsex use with chlamydia (p=0.003) and gonorrhoea (p=0.030).Conclusions We observed an unbalanced access to PrEP in respect to all key populations which might benefit from PrEP, with a similar choice for event-based or daily-based regimens. High-risk behaviours and STIs were frequently observed. History of chlamydia was very frequently high in asymptomatic MSM at BL, compared with what observed before access to PrEP. High-risk behaviours and HIRI-MSM were associated with most of STIs.